THE DEVELOPMENT AND TRANSFORMATION OF THE MONGOLIAN PARTY SYSTEM, 1992–2020 - Pavel Maškarinec (Politology, 2023)
Since its democratization in 1990 (see Fish 2001; Fritz 2002; Fritz 2008; Fish and Seeberg 2017; Aagaard Seeberg 2018), Mongolia has held eight elections (1992–2020) to its unicameral parliament – the Great State Khural. Previously, Mongolia’s electoral system has attracted only scant attention in comprehensive comparative studies of electoral institutions (Maškarinec 2017; Maškarinec 2019a; Jacob and Schenke 2020) and of politics generally (Croissant 2007; Reilly 2007; Croissant and Schächter 2010; Croissant and Völkel 2012), although Mongolia is one of the few countries (if not the only one) of post-communist Asia which experienced successful long-term democratization and consolidation (Fish 2001; Fritz 2002; Schneider and Schmitter 2004; Soni 2013). The success of these processes was not precluded even though the country lacked the many prerequisites which are normally considered favourable for democratization (see Fish 1998).